The User Experience of an Electronic Medical Record: A Cross-Sectional Study in the Public Health Sector of the Western Cape, South Africa - Gumede, Sinenhlanhla; Dyers, Robin (Journal of Health Informatics in Africa, 2024)
Background and Purpose: The Electronic Continuity of Care Record (eCCR) is a web-based Electronic Medical Record commissioned and implemented by the Western Cape Government Health and Wellness department in 2015 for all 53 public hospitals in the province to capture medical records of patients. While there has been previous research into the quality of clinical coding capture within the eCCR, there has not yet been a formal evaluation of end users’ experience (UX) of the application. This study is the first to formally evaluate the user experience of an eHealth application in the public sector in the Western Cape. This study evaluated the user experience of the eCCR end users in terms of its attractiveness, pragmatic qualities (efficiency, perspicuity, dependability) and hedonic qualities (stimulation, novelty), describes the characteristics of end users and explores associations between user characteristics and the UX of eCCR.Methods: A validated UX Questionnaire survey was made available online to evaluate the eCCR user experience. An invitation and link to the survey was added on the eCCR landing webpage specifically to target users of the application. Response data were collected over three months from June to August 2023 using 26 UEQ questions that comprised Lickert-type scales of 1-7 to rate experience. The mean was determined for each scale. Mean scale values > 0,80 represented a positive experience. Values between -0.80 and 0.80 represented neutral experience while values < -0,80 represented a negative experience.Results: There were 201 participants in this study. The question (item) response means were combined per scale: attractiveness=0.87, perspicuity=1.32, dependability=0.88, stimulation=0.76, efficiency and novelty reported low means of 0.55 and 0.30 respectively. Conclusion: The User Experience UX evaluation indicated that the eCCR was an easy-to-learn and understandable web-based application, the end users reported it was valuable, secure, enjoyable, and met user expectations. The overall attractiveness of application was positive. The pragmatic qualities of the eCCR were rated higher than the hedonic qualities. The study indicated that the eCCR can be strengthened with regard to its innovative and creative features to improve upon the experience scales related to novelty, as well as its efficiency.